A Plaidoyer on State Bankruptcy: Between Economic Reality and Legal Impossibility - Dejan Bodul; Pavle Jakovac; Marko Tomljanović (LeXonomica, 2024)
The history of financial crises and their serious consequences have made them a key interest for both academics and policymakers. During periods of economic growth, bankruptcy was mainly viewed as a mechanism to eliminate uncompetitive firms. However, current global economic conditions, including inflation, decreased demand, rising production costs, the energy crisis, and financial collapses in certain markets, have made it difficult for many companies to service their debts. Outdated bankruptcy regulations have worsened the situation. In the context of globalization and the internationalization of business, modernizing bankruptcy laws has become essential. Various international institutions have advocated for reforms, including redefining the concept of state bankruptcy. This paper aims to analyze the role of the state in bankruptcy, focusing not on its role as a commercial creditor or debtor but as a potential subject of bankruptcy itself.PovzetekZgodovina finančnih kriz in njihove resne posledice so postale ključnega pomena za akademike in oblikovalce politik. V obdobjih gospodarske rasti se je na stečaj gledalo predvsem kot na mehanizem za izločitev nekonkurenčnih podjetij. Vendar so sedanje svetovne gospodarske razmere, vključno z inflacijo, zmanjšanim povpraševanjem, naraščajočimi proizvodnimi stroški, energetsko krizo in finančnimi zlomi na nekaterih trgih, mnogim podjetjem otežile odplačevanje dolgov. Zastareli stečajni predpisi so razmere še poslabšali. Zaradi globalizacije in internacionalizacije poslovanja je posodobitev stečajne zakonodaje postala nujna. Različne mednarodne institucije so se zavzele za reforme, vključno s ponovno opredelitvijo koncepta državnega stečaja. Namen tega prispevka je analizirati vlogo države v stečaju, pri čemer se ne osredotočamo na njeno vlogo kot poslovnega upnika ali dolžnika, temveč kot potencialnega subjekta samega stečaja.